An empirical investigation of customer satisfaction with multi channel banking. (20th May 2009) - Jham, Vimi
Banks in India have succeeded in promoting new services to its customers. The likelihood of current customers is tempted to do business online. The study sought to investigate factors that influenced Indian bank customers' adoption of three major banking channels, i.e., branch banking, ATM and internet banking. Based on extant literature on bank marketing and interviews with bank managers in India, a questionnaire was designed. Then, in a large-scale survey by means of personal and telephone interviews, data was obtained from bank customers. This paper focuses on the adoption of multi channel banking by existing banks customers through an investigation of the factors that influence customer's acceptance of multi channel banking services. An exploratory study of the Indian customers in six banks is conducted to identify the factors which lead to adoption of multi channel banking services with the help of data reduction technique called factor analysis.